A Discourse Analysis of Cohesion Devices an Students’ Writing of Recount Text - Tungky Ariwibowo; Didin Nuruddin Hidayat; Nida Husna; Alek Alek; Agus Sufyan (STABN RADEN WIJAYA WONOGIRI, 2023)
This study aimed to determine the types of cohesive devices utilised in the recount text writing of Tenth-grade students at MAN Huta Godang during the academic year 2022/2023 and to identify the most prevalent form of cohesive device. The data was taken from 5 students writing. The study employed a qualitative descriptive method that includes cohesive devices in students' writing. It was found that the types of grammatical cohesion were reference, conjunction, and ellipsis. The most frequently used type of grammatical cohesion is the reference. Students who recount text writing using grammatical cohesion can be in the